An IoT-Based Soil Moisture Monitoring Prototype with Automated Notifications for Drought Risk Indication - Muhammad Amirul Mu'min; Dahlan (Ran Edu Center, 2025)
Soil moisture monitoring is a critical aspect of sustaining crop cultivation, particularly in environments that are vulnerable to climate variability and fluctuations in soil water content. The limitations of manual monitoring methods, which are often inefficient and time-consuming, highlight the need for automated systems capable of delivering timely and accurate information. This study aims to develop and evaluate an IoT based soil moisture monitoring system equipped with automatic notification capabilities for users. The proposed system employs an ESP32 microcontroller as the main processing unit, soil moisture sensors for data acquisition, MQTT as the data communication protocol, and a Telegram Bot as the notification service. The research methodology includes system architecture design, sensor data processing, internet network integration, and the implementation of automated notification services. Experimental testing was conducted to assess the consistency of sensor readings, the reliability of data transmission, and the system’s responsiveness to changes in soil moisture levels. The results demonstrate that the system is able to deliver real-time soil condition information with good stability and to respond to critical decreases in soil moisture through automatic notifications within a relatively short response time. These findings indicate that an IoT-based approach can enhance the efficiency of environmental monitoring and support informed decision-making in crop management. The developed prototype shows potential for application in precision agriculture as well as small- to medium-scale environmental monitoring scenarios.